(untitled) (Research, Society and Development, 2020)
Gummy candies are nutritionally poor foods; however, they have a large consumer market. Enhancing these products with nourishing and/or functional matrices is a challenge. This study aimed to develop the features of a gummy candy probiotic, containing Bifidobacterium lactis HN019, and evaluate its effectiveness in inhibiting Streptococcus mutans UA159. The candy was suitable for probiotic development, whose viable bacterial count was 8.54 Log CFU/g in the ready-to-eat product; high viability was maintained during the 28-day shelf life. Additionally, the rate of probiotic survival under in vitro gastrointestinal simulation was 98% and 93% in the ready-to-eat product and after shelf life, respectively. The sensory analysis revealed scores over 8.0 in all attributes evaluated. Lastly, the inhibition test of S. mutans UA159 showed 25% and 98% inhibition, with 10% and 20% xylitol respectively. Probiotic and xylitol gummy candy is a potential functional food and can target a niche food market, such as teenagers.